Perception Regarding Gender Bias in Tribal Community of Tapi District of South Gujarat, Western India - Patel, Amit; Patel, Fenil; Patel, Prakash; Patel, N B; Bansal, R. K. (National Journal of Community Medicine, 2014)
Introduction: Gender bias is strikingly apparent in educational access, employment avenues and representation in the field of politics. In fact violation of the rights of a girl child is rampant and this extends to the whole spectrum from foeticide to neglect to labour to trafficking, rape and eventually ends with her death. This study was conducted to know perception regarding various aspects associated with female gender bias and the awareness among respondents on prevailing schemes for the benefit of women. Methodology: This was a cross-sectional descriptive study conducted in Tribal District of Tapi in 2013 using a semi-structured interview schedule. Data was entered in Microsoft Excel 2003 and was analyzed in Statistical Package for Social Sciences (SPSS) software version 16. Result: It was remarkably observed that 121(80.7%) has no gender preference for their 1st child, 17(11.3%) participants has female child preference while 12(8.0%) has male child preference for their 1st child. 137(91.3%) participants were aware of the fact that the repeated prenatal sex diagnosis and abortions are detrimental to the mental and physical health of a woman. Conclusion: Most of the participants have no gender preference as first child. Good awareness was found regarding the prenatal sex determination test. Most common answer for the desire for male child was to run the family tree.